Efficacy of EUS-RFA in pancreatic tumors: Is it ready for prime time? A systematic review and meta-analysis - Dhaliwal, Amaninder; Kolli, Sindhura; Dhindsa, Banreet Singhg; Choa, Jacqueline; Mashiana, Harmeet Singh; Ramai, Daryl; Chandan, Saurabh; Bhogal, Neil; Sayles, Harlan; Bhat, Ishfaq; Singh, Shailender; Adler, Douglas G. (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) can be used in patients with unresectable pancreatic ductal adenocarcinoma (PDAC). We performed a systematic review and meta-analysis to evaluate the efficacy of EUS-RFA in treatment of locally advanced unresectable PDAC and other pancreatic tumors.Patients and methods A comprehensive search was done of multiple electronic databases and conference proceedings including PubMed, EMBASE, Web of Science databases, Google Scholar and manual search of references (from inception through May 2019) to identify the studies reporting use of EUS-RFA for pancreatic lesions. The primary outcome was to evaluate technical and clinical success of the procedure. The secondary outcome was to study overall adverse events (AEs).Results Thirteen studies reporting 165 EUS-RFA procedures on 134 patients were included. Of 134 patients, 27.94 % (38) had unresectable locally advanced PDAC, 40 % (53) had PNETs, 3 % (4) had metastasis to the pancreas and 30 % (41) had other lesions. The pooled technical success rate calculated out of the total number of procedures was 100 % (95 % CI [99.18 – 100], I2 = 0 %). The pooled clinical success rate calculated out of the total number of patients was 91.58 % (95 % CI [82.5 – 98.08], I2 = 21.5 %). The pooled overall AE rates were 14.67 % (95 % CI [4.77 – 27.46], I2 = 56.19 %) out of which abdominal pain was the most common with 9.82 % (95 % CI [3.34 – 18.24], I2 = 23.76 %). Low to moderate heterogeneity was noted.Conclusion EUS-RFA has high technical (100 %) and clinical success (91.5 %) rates. Further multicenter trials are needed to further validate our findings.